2015
DOI: 10.1021/acs.jpclett.5b00901
|View full text |Cite
|
Sign up to set email alerts
|

Density and Compressibility of Liquid Water and Ice from First-Principles Simulations with Hybrid Functionals

Abstract: We determined the equilibrium density and compressibility of water and ice from first-principles molecular dynamics simulations using gradient-corrected (PBE) and hybrid (PBE0) functionals. Both functionals predicted the density of ice to be larger than that of water, by 15 (PBE) and 35% (PBE0). The PBE0 functional yielded a lower density of both ice and water with respect to PBE, leading to better agreement with experiment for ice but not for liquid water. Approximate inclusion of dispersion interactions on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
98
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(109 citation statements)
references
References 83 publications
(196 reference statements)
10
98
1
Order By: Relevance
“…Fig. 2b) and total densities are shifted to larger values (in agreement with AIMD simulations performed at a single state point [38,40,47]), reducing deviations from experiment to 5 -10 %. Moreover, a density minimum in the super- cooled regime (at ≈200 K and ≈215 K for BLYP-vdW and RPBE-vdW, respectively) can be identified that is consistent with experimental measurements of water confined in silica pores [37] and simulations using empirical water models [7,8].…”
Section: A Neural Network Potentialssupporting
confidence: 83%
“…Fig. 2b) and total densities are shifted to larger values (in agreement with AIMD simulations performed at a single state point [38,40,47]), reducing deviations from experiment to 5 -10 %. Moreover, a density minimum in the super- cooled regime (at ≈200 K and ≈215 K for BLYP-vdW and RPBE-vdW, respectively) can be identified that is consistent with experimental measurements of water confined in silica pores [37] and simulations using empirical water models [7,8].…”
Section: A Neural Network Potentialssupporting
confidence: 83%
“…Related work has shown that revPBE gives even lower densities [144,276], with ρ eq ranging from 0.69 to 0.85 g/cm 3 . PBE also underestimates the density [144,273,276,[278][279][280], but more modestly, with ρ eq varying from 0.86 to 0.96 g/cm 3 in different studies. One of the few DFT studies of the moderately compressed liquid is that of Ref.…”
Section: Ggas and Hybridsmentioning
confidence: 99%
“…In contrast, the intermediate-and long-ranged parts of the vdW interactions have not been captured by any general-purpose GGA. Recent studies have identified vdW interactions as an important determinant of water structure; vdW interactions often lead to more disordered water structures, more accurate water densities, and improved dynamic properties (11,(24)(25)(26)(28)(29)(30). Thus, the H-bond network of liquid water is produced by a delicate competition among covalent bonds, H bonds, and vdW interactions, and describing this complex interplay of interactions continues to be a highly challenging task.…”
Section: Significancementioning
confidence: 99%